Numeryczne Rozwiązywanie Zagadnień Sprężysto-Plastycznych Metodą Lokalnych Wariacji - Czernousko, F.L. (Engineering Transactions, 1972)
The paper is devoted to the method of local variations for numerical solutions of variational problems and to some applications of this method to the problems of elasticity and plasticity.